Liberia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper reviews the recent economic developments, production, prices, and employment of Liberia. It also highlights the fiscal, monetary, and external sector developments, and the failures and credibility in the banking system. It describes the role of timber, rice, petroleum, and cement in the Liberian economy. It also provides the details of the IMF's projections and estimates on Liberia's summary of the tax system, central government revenue, and economic classification of central government expenditure, summary of accounts of the central bank of Liberia, and deposit money banks during March 2001-September, and so on.